(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the analgesic efficacy of a single-shot right-sided erector spinae plane block using 0.25% Levobupivacaine in minimally invasive cardiac surgery in children. Subjects and Methods: A total of 30 pediatric patients diagnosed with ventricular septal defect or atrial septal defect, indicated for minimally invasive cardiac surgery, received a single-shot right-sided erector spinae plane block with 0.25% Levobupivacaine. The study was conducted at the Vietnam National Children’s Hospital from September 2024 to August 2025. Results: The patients had a mean age of 30.9 ± 21.9 months and a mean weight of 13.2 ± 9.2 kg; 60% were female; ventricular septal defect accounted for 56.7% and atrial septal defect 43.3%; most patients were classified as heart failure grade I (66.7%). The average duration of anesthesia was 251.2 ± 34.9 minutes, surgical time 141 ± 33.4 minutes, and time to extubation 26.0 ± 12.5 minutes. The intraoperative Fentanyl dose was 4.3 ± 1.9 mcg/kg and 24-hour postoperative Fentanyl consumption was 23.1 ± 1.7 mcg/kg. Sedatives were not required in 67% of cases. All patients were pain-free at 24 hours postoperatively. No complications were reported. Intensive care unit stay ranged from 1-2 days, and the average hospital stay was 10 days. Conclusion: Single-shot right-sided erector spinae plane block with 0.25% Levobupivacaine is a safe and effective analgesic technique that provides good pain control and promotes early recovery.